Low‐energy technology for producing anhydrite in the CaCO3–H2SO4–H2O system derived from industrial wastes. Issue 7 (13th April 2021) - Kamarou, Maksim; Korob, Natalia; Hil, Anastasiya; Moskovskikh, Dmitry; Romanovski, Valentin
Abstract: BACKGROUND: A high‐quality anhydrite binder could be produced due to the exergy of sulfuric acid in the CaCO3 –H2 SO4 –H2 O system derived from industrial wastes. Waste of sulfuric acid derived from the production of heat‐resistant fibers and wastes of limestone that was formed on the metallurgical enterprise were used for the synthesis of anhydrite. Such a product is safe from an environmental point of view and has many advantages, both operational and economic, over standard gypsum binders. RESULTS: The optimal technological parameters have been established and a technological scheme for producing anhydrite excluding the stage of calcium sulfate dihydrate formation has been proposed. Anhydrite production in the CaCO3 –H2 SO4 –H2 O system, due to the exergy of sulfuric acid, is a promising technology to replace the traditional thermal technology for producing anhydrite. This technology can reduce fuel costs because the required synthesis temperature is 95–105 °С, instead of 800–1000 °С in the traditional one, and this significantly reduces the cost of manufactured products. CONCLUSION: The maximum yield of synthetic anhydrite was provided by a limestone suspension taken in a stoichiometric amount. This neutralizing agent makes it possible to obtain particles of a prismatic shape, the size of which is generally more than 20 μm. © 2021 Society of Chemical Industry (SCI).